Penerapan Pembelajaran Problem Solving Untuk Meningkatkan Hasil Belajar IPS Pada Rombongan Belajar Siswa - Nurazizah, Nurazizah; Saputra, Yudha Munajat; Kurnia, Dadang (Jurnal Pena Ilmiah, 2021)
The study is motivated by the low social studies learning outcomes of students. on of the reasons is that the implementation of learning applied by teachers is conventional and less creative.this study aims to improve student learning outcomes in social studies learning of fifth grade by implementing problem-solving learning. The study used descriptive qualitative as a method. The study was held at SD NegeriBabakanHurip. Data collection techniques used are observation, interviews, and documentation. The result shows that there is an increase in student learning outcomes of social studies learning. The implementation of problem-solving learning can improve student learning outcomes. With the implementation of problem-solving learning, there is affection on student learning outcomes at SDN BabakanHurip. Based on the study results, it has been carried out that the implementation of problem-solving learning can improve social studies learning outcomes on the Japanese Occupation in Indonesia material in fifth-grade SDN BabakanHurip. The implementation of problem-solving learning can be used as a reference for innovative and interesting learning.Â